EFEK HUBUNGAN PARASOSIAL PENGGEMAR KOREAN POP DI MEDIA SOSIAL TWITTER (Studi Deskriptif pada Fandom EXO-L Samarinda) - Mega Puspita Sari; Silviana Purwanti; Nurliah Nurliah (MEDIAKOM : Jurnal Ilmu Komunikasi, 2022)
Pseudo-relationship that created by EXO-Ls as fans and audiences with their media character, EXO through social media Twitter, is called a parasocial relationship. Through social media Twitter, fans can find out a real-time information and can interact with EXO, where in parasocial relationships the effects are sense of companionship, personal identity, pathological attitudes, pseudo-friendship, and behavioral guidelines. This research aims to find out, describe and analyze how the effects of parasocial relationships that occur on EXO fans, namely EXO-L in the city of Samarinda on Twitter. This research uses descriptive qualitative research with data collection techniques in the form of purposive sampling to obtain maximum information and data. Using Hoffner's Parasocial theory and Horton and Wohl's Parasocial theory, the results of this study indicate that the effects of parasocial relationships that occur in EXO-L Samarinda on Twitter are sense of companionship, personal identity, pathological attitudes, pseudofriendship, and behavioral guidelines.